Implementation of Fast Track Method to Accelerate Construction Project Scheduling - Muin, Suriati Abd.; Watono; Alimuddin, Evi Gusmiarni; Ridwan, Siti Huriyah Shatara (Politeknik Negeri Ujung Pandang, 2024)
In a project, the planning stage is the key to success because it determines the allocation, funding, time and quality to be achieved. In order for work efficiency and effectiveness to be fulfilled properly, the implementation of the project is influenced by planning and scheduling factors. Construction project control is a systematic activity or effort to determine standards that are in accordance with the planning objectives, compare implementation with planning, and make necessary corrections so that costs, resources, and time can be used effectively and efficiently in order to achieve the desired construction project goals. If there is an imbalance between the plan and the realization of the work, then the project may experience delays like what happened to the Lantamal VI Makassar Naval Pier project. The project experienced several delays in work and required rescheduling, so a special method was needed that could speed up the project implementation time. The purpose of this study is to accelerate the duration of work and get project costs after implementing the fast track method. The results of implementing the fast track method can reduce the time by 64 days or experience a time acceleration of 20.9% from the initial duration of 306 days, the total project cost before the acceleration is Rp. 50.365.788.654,89 After acceleration with the fast track method which affects the overhead cost to Rp. 49,312,386,539, the total cost reduced is Rp. 1,053,402,116 or a savings of 2.09% of the total cost.